Evaluation of a reverse tetracycline inducible system in recombinant BCG to improve stability and immunogenicity - Mbele, Prisca (Division of Virology, 2015)
The aim of this study is to utilise the tetracycline dependent gene regulation system to down-regulate recombinant antigen expression in BCG during the expansion of seed stocks and up-regulate expression prior to or post vaccination.